Clinical Efficacy and Safety Profile of Anterior Thalamic Stimulation for Intractable Epilepsy - Sobstyl, Michał; Stapińska-Syniec, Angelika; Iwański, Szczepan; Rylski, Marcin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Introduction Deep brain stimulation of the anterior nucleus of the thalamus (ANT DBS) is a neuromodulation therapy for patients with refractory partial seizures. The ANT is the structure of a limbic system with abundant neuronal connections to temporal and frontal brain regions that participate in seizure propagation circuitry.State of the Art We have performed a literature search regarding the clinical efficacy of ANT DBS. We discuss the surgical technique of the implantation of DBS electrodes with special attention paid to the targeting methods of the ANT. Moreover, we present in detail the clinical efficacy of ANT DBS, with a special emphasis on the stimulation parameters, a stimulation mode, and polarity. We also report all adverse events and present the current limitations of ANT DBS.Clinical Implications In general, the safety profile of DBS in intractable epilepsy patients is good, with a low rate of surgery, hardware-related, and stimulation-induced adverse events. No significant cognitive declines or worsening of depressive symptoms was noted. At long-term follow-up, the quality-of-life scores have improved. The limitations of ANT DBS studies include a limited number of patients treated and mostly open-label designs with only one double-blind, randomized multicenter trial. Most studies do not report the etiology of intractable epilepsy or they include nonhomogeneous groups of patients affected by intractable epilepsy. There are no guidelines for setting initial stimulation parameters. All the variables mentioned may have a profound impact on the final outcome.Conclusions ANT DBS appears to be a safe and efficacious treatment, particularly in patients with refractory partial seizures (three-quarters of patients gained at least 50% seizure reduction after 5 years). ANT DBS reduces most effectively the seizures originating in the temporal and frontal lobes. The published results of ANT DBS highlight promise and hope for patients with intractable epilepsy.
Keywords: intractable epilepsy; anterior nucleus of the thalamus; deep brain stimulation; thalamic stimulation